Improving Learning Outcomes Passing Up In Game Volleyball Target Through Ring Model For Class VIII students SMP Budi Mulia School Year 2019/2020: Improving Learning Outcomes Passing Up In Game Volleyball Target Through Ring Model For Class VIII students SMP Budi Mulia School Year 2019/2020 - Ika Puspita Sari Endah (Journal of Midwifery and Nursing, 2020)
The research was conducted in SMP Budi Mulia Terrain Academic Year 2019/2020. This study was conducted in two cycles, with each cycle comprising the implementation of the action in the form of learners passing through Model Top Volleyball Ring Target tailored to the subject matter. Subjects in this study is a class VIII SMP Budi Mulia Terrain academic year of 2019/2020 with a research subject as many as 30 people. The method of research is a classroom action (Classroom Action Research). To obtain the data in this study is carried achievement test I and II shaped teshasil Ring learn the basic techniques of passing target on volleyball as much as two meetings. After the initial data collected is of 30 students who have learning completeness only 19 people (79%) while the remaining 11 students (67%) has not been completed, so do the analysis of the obtained results of the analysis: (1) In the first cycle after test results can be seen that the first study of 30 students who are the subject of this research, it turns out 20 students (66.67%) who own mastery learning, while the rest are 10 students (33.33%) have not had a mastery learning. -Rata average value obtained was only 60.64. (2) In the second cycle can be seen that the turns of 30 students, there are 27 students who completed (90%) who own mastery learning, while the rest are 3 students (10%) do not yet have complete learned. Value - average earned only reached 74.64.